Prevalence of Salmonella sp. in African Catfish (Clarias gariepinus) obtained from farms and wet markets in Kelantan, Malaysia and their antibiotic resistance - Chia, Kim Sing; Md. Zahirul Islam Khan,; Hassan Hj. Mohd Daud,; Abd Rahman Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The present study was conducted to determine the prevalence and antibiotic resistance of Salmonella sp. isolated from African catfish (Clarias gariepinus). A total of 30 catfish were harvested from four different farms and four different wet markets. A total of 60 samples (30 catfish skins and 30 catfish intestines) were used for Salmonella sp. isolation (pellet-method), its biochemical and serological test. Confirmation of Salmonella sp. were determined by polyvalent O antisera and polymerase chain reaction (PCR) using genus specific primers for invA genes (DNA amplification showed one distinct band with molecular weight of 389 bp) and the species of isolated Salmonella sp. were identified by serotyping. The result showed 6/30 (20%) of fish or 6/60 (10%) of organ samples were positive for Salmonella sp. Among those positive for Salmonella sp., 4/6 were from intestine samples and 2/6 were from skin samples. No significant difference was found in the prevalence of Salmonella sp. isolates between fish harvested from farms and wet markets (p-value= 0.406). The Salmonella serovars identified were Salmonella corvallis (n=3), Salmonella mbandaka (n=2) and Salmonella typhmurium (n=1). Salmonella sp. isolates were resistance to Penicillin (P 10, 100%), Clindamycin (DA 2, 100%), Tetracycline (TE 30, 100%) and Rifampicin (RD 5, 100%) and all of the isolates were susceptible or intermediate resistance to Ceftazidime (CAZ 30) and Trimethopin (W 5). Multiple antibiotic resistance (MAR) index of all Salmonella sp. isolates in current study was 0.67 indicating that fish sampled in the present study was under high risk of been exposed to the tested antibiotics.